1990
DOI: 10.1111/j.1399-3054.1990.tb06742.x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium interactions with K+(86Rb+) and 45Ca2+ fluxes in three cultivars of sugar beet (Beta vulgaris)

Abstract: Three cultivars of sugar beet (Beta vulgaris L.), which are sensitive to aluminium (Al) in the order Primahill > Monohill > Regina, were grown in water culture for 2 weeks. Nutrients were supplied at 15% increase of amounts daily, corresponding to the nutrient demand for maximal growth. The 2.4‐dinitrophenol (DNP)‐sensitive (metabolic) and DNP‐insensitive (non‐metabolic) uptake of aluminium, phosphate. 45Ca2+ and K+(86Rb+) in roots were measured as well as transport to shoots of intact plants. All 3 cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
1
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 43 publications
2
21
1
2
Order By: Relevance
“…It is also encouraging to note that the net current predicted from summing the ion fluxes in (5,30,32), and some evidence suggests a competitive interaction between Al and Ca2' at the membrane surface (6,10,18). However, in the present work, Al had no effect on Ca2+ influx in five of seven experiments.…”
Section: Identity Of the Current-carrying Ionssupporting
confidence: 62%
“…It is also encouraging to note that the net current predicted from summing the ion fluxes in (5,30,32), and some evidence suggests a competitive interaction between Al and Ca2' at the membrane surface (6,10,18). However, in the present work, Al had no effect on Ca2+ influx in five of seven experiments.…”
Section: Identity Of the Current-carrying Ionssupporting
confidence: 62%
“…However, the Al content in the mature regions of the sensitive roots was only twofold higher than in the mature regions of the tolerant roots (Fig. 4) (12,15,26,29). Wagatsuma (26) and Pettersson and Strid (15) suggested that DNP changed the plasma membrane permeability, increasing the passive transport of Al.…”
Section: Discussionmentioning
confidence: 98%
“…therein). In an Al-resistant sugar beet cultivar Lindberg (1990) speculated that a metabolically dependent efflux of Pi was occurring in the presence of Al. Also, Pettersson andStrid Plant Physiol.…”
mentioning
confidence: 99%